COVID-19 and freedom of information: The return of the leviathan - Marsili, M. (2022)
This paper aims to shed light on the right to information and the freedom of the media in the context of the COVID-19 outbreak. Infection disease outbreaks are invariably characterized by myths and rumors, boosted by social media accounts, that media often pick up and circulate. Under the justification to avoid panic and confusion, and to combat “fake news” during the COVID-9 pandemic, some governments took emergency measures that curtail the freedom of information. The lack of a legal definition of the term “fake news” leaves room for arbitrary and broad interpretations. Decrees issued during the state of emergency – including the practice of detaining journalists for their work and the abuse of pre-trial detention and Internet censorship – sound like measures adopted to restrict the freedom of expression and the freedom of the media, and to shout down dissenting voices. Any kind of pressure against journalists has an immediate consequence, not only on them but also on the public’s right to be informed. Media play a key role in providing important information to the public, and a pluralistic and vibrant media landscape is indispensable to any democratic society. Access to information and a free working environment are therefore essential and need to be ensured at all times, even under state of emergency. Authorities cannot invoke the state of emergency or national security as a motivation to suspend or limit fundamental human rights. The fight against COVID-19 can be a pretext for restricting civil liberties.